Study of coronary sinus and its tributaries in pigs - Reyes , Diana Marcela; Rivera, Jairo José; Gómez , Fabián Alejandro; Cortes, Luz Stella (Spei Domus, 2015)
Introduction. Similarities between the bodies of pigs and humans have encouraged studies in comparative anatomy, trying to describe in detail the anatomical variations that could influence in the xenotransplantation, given that advances in genetics, immunology and biotechnology are large, this possibility is not far. The objective of this work was to make contributions to the vascular study of porcine heart.  Methodology. 60 porcine hearts, with an average of 5 months old and weighing 85-95kg were obtained from plant Vijagual. After receipt hearts were kept in water for 6 hours, then they were perfused with polyester resin semi-synthetic and mineral blue color, moreover the left coronary artery was perfused with red mineral color. Subsequently, the hearts were subjected to a process of partial corrosion with potassium hydroxide (15%), then the coronary sinus and its tributary branches were dissected from its origin to its distal segments, path, shapes, sizes, anastomosis and presence of registered anatomical variations. Photographic record of the samples was performed. Results. The distal caliber of Great cardiac vein (5.36 +/- 1,04mm), its origin was determined from the apex at 70% of anatomical pieces it studied was determined and the ventricular groove paraconal 30% of the pieces analyzed. The arteriovenous trigone was found in 58 of cardiac structures studied (96.66%).Conclusion. The description of the anatomic variations present in the pig heart structure will contribute to the possibility of xenotransplantation and also provides data for the development of studies on cardiovascular surgery and certain diseases of clinical and epidemiological importance.
Keywords: cardiac circulation; Coronary sinus; comparative anatomy; Heart; venous circulation